2019
DOI: 10.1007/978-3-030-24766-9_26
|View full text |Cite
|
Sign up to set email alerts
|

Reconfiguring Undirected Paths

Abstract: We consider problems in which a simple path of fixed length, in an undirected graph, is to be shifted from a start position to a goal position by moves that add an edge to either end of the path and remove an edge from the other end. We show that this problem may be solved in linear time in trees, and is fixed-parameter tractable when parameterized either by the cyclomatic number of the input graph or by the length of the path. However, it is PSPACE-complete for paths of unbounded length in graphs of bounded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…3. Simultaneously to our work,Demaine et al (2019) also studied reconfiguration of undirected paths and found that path reconfiguration is fixed-parameter tractable when parameterized by the length of the path.…”
mentioning
confidence: 75%
“…3. Simultaneously to our work,Demaine et al (2019) also studied reconfiguration of undirected paths and found that path reconfiguration is fixed-parameter tractable when parameterized by the length of the path.…”
mentioning
confidence: 75%
“…It would be also interesting to know whether Directed Path Reconfiguration and Directed Path Sliding are fixed-parameter tractable (FPT) parameterized by the length of input paths. Although the undirected counterparts are known to be FPT [3,4], it would be difficult to apply their techniques directly to our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they showed that if S(G) consists of all trees in G, every instance of the corresponding reconfiguration problem is a yes-instance unless the two input trees have different numbers of edges. Motivated by applications in motion planning, Biasi and Ophelders [1], Demaine et al [3], and Gupta et al [4] studied some variants of reconfiguring undirected paths and showed that these problems are PSPACE-complete, while they are fixed-parameter tractable (FPT) when parameterized by the length of input paths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other results on reconfiguration of paths are known in the literature. For example, Demaine et al [7] proved that the reachability problem for shifting paths (“Given two paths in a graph, can one be transformed into the other one by a sequence of shifts?”) is sans-serifPSPACE‐complete. For shortest u,v‐paths, for which each transformation consists in changing a single vertex, the same result was obtained by Bonsma [5].…”
Section: Introductionmentioning
confidence: 99%